Canadian Bank Unionism: Perspectives and Issues - Ponak, Allen; Moore, Larry (Relations industrielles / Industrial Relations, 1981)
This paper aims at providing an adequate foundation for ad-dressing practical and theoretical industrial relations issues likely to be important to the banking industry in the future.